Ecophysiological evaluation of intrapecific competition of Cenchrus ciliaris L. (Poaceae) in pots - Vera, A.=700 1 Medrano, C.; Del Villar, A.; Paz, V.; Paez, A.
(Es, En)
Ilus., 18 ref.
Keywords: CENCHRUS CILIARIS; COMPETENCIA BIOLOGICA; MALEZAS; VENEZUELA; PASTOS